Triglyceride to high-density lipoprotein cholesterol ratio as a marker of non-alcoholic fatty liver disease in type 2 diabetes - Dwitama Adiwinoto, Robert; Pranoto, Agung; Sugihartono, Titong; Adi Soelistijo, Soebagijo; Pratama Adiwinoto, Ronald (International Journal of Public Health Science (IJPHS), 2024)
Type 2 diabetes mellitus (T2DM) and non-alcoholic liver disease (NAFLD) shared a common feature, insulin resistance (IR), which is marked by a change in the lipoprotein fraction, namely increased triglycerides (TG) and decreased high-density lipoprotein cholesterol (HDL-C) levels. Blood lipids are routinely examined in T2DM patients; thus, our study aimed to investigate the performance of TG/HDL-C ratio values to identify hepatic steatosis, the earliest manifestation of nonalcoholic fatty liver disease (NAFLD), in T2DM patients. One hundred adult T2DM patients over 30 years old were recruited from the diabetes outpatient clinic at the Dr. Soetomo General Academic Hospital from August to October 2023. Data regarding sociodemographics, medication, glycosylated hemoglobin (HbA1c), lipid profiles, and FibroScan with controlled attenuation parameter (CAP) were collected from all participants. The group with hepatic steatosis (CAP≥237 dB/m) had a higher body mass index (BMI), higher TG levels, and TG/HDL-C ratio values. The TG/HDL-C ratio was significantly correlated with CAP values. Hepatic steatosis can be identified using the TG/HDL-C ratio with a cut-off value of 2.83 (sensitivity:72.4%; specificity:71.4%). An elevated TG/HDL-C ratio is associated with a higher risk (OR:6.562; p<0.05) of having hepatic steatosis. The TG/HDL-C ratio is a potential marker to predict NAFLD in T2DM patients.